A comprehensive review on blockchain and Internet of Things in healthcare. Issue 10 (10th August 2021) - Sharma, Aashima; Kaur, Sanmeet; Singh, Maninder
Abstract: Blockchain Technology, the fundamental technology behind Bitcoin, has drawn considerable recognition ever since its origin. Its potential has gained significant interest in various applications, varying from the music industry, financial services, Internet‐of‐Things (IoT), smart grid, edge computing, cybersecurity, and the healthcare industry. However, the information is divided amongst several intermediaries involved with adverse impacts on data quality in the healthcare domain. In the near future, blockchain technology can reshape the way the healthcare industry works by providing personalized and reliable patient data management, reforming the traditional healthcare practices, secure mechanisms for data sharing, efficient pharmaceutical supply chain management, and drug traceability and many more. In this study, an extensive literature review has been provided that includes the different prospects of using blockchain technology in healthcare. The review investigates the work done to enable the amalgamation of IoT and Blockchain in the health ecosystem. Significant blockchain‐based healthcare use cases such as data storage, data sharing, drug traceability, clinical trials, and remote patient monitoring are investigated. Further, the Internet of Things and blockchain technology‐based SWOT (Strength, Weakness, Opportunity, and Threat) analysis and the challenges linked in the healthcare domain because of the enactment of IoT and blockchain technology are discussed to support advanced studies in this domain. Abstract : In this study, an extensive literature review has been provided that includes the different prospects of using blockchain technology in healthcare. The review investigates the work done to enable the amalgamation of IoT and Blockchain in the health ecosystem. Significant blockchain‐based healthcare use cases such as data storage, data sharing, drug traceability, clinical trials, and remote patient monitoring are investigated.